PENGARUH DAU, DAK, PDRB, DAN INFLASI TERHADAP KEMANDIRIAN KEUANGAN DAERAH PROVINSI JAWA BARAT - Hakim, Albert Alexander; Busnetty, Ida (Neolectura, 2024)
This study aims to see how the realisation of the General Allocation Fund (DAU), Special Allocation Fund (DAK), Economic Growth (GRDP), and Inflation impacts the level of regional financial independence, with a special emphasis on districts and cities in West Java Province. For data analysis, the Fixed Effect model was used for panel data regression. The research sample consists of all districts/municipalities in West Java Province (total sampling) that have DAU and DAK realisation, as well as GRDP and inflation, which are the components that make up the regional financial independence ratio from 2018 to 2023. DAK, DAU, and inflation have no impact on the level of regional financial independence, but the analysis results show that GRDP has a significant positive impact.